Design of the robot mechanism for quality acceptance of insulator installation in 500 kV transmission lines - LI Yu; ZHANG Zhongjie; ZHOU Xiaofa; CHEN Shufan; SUN Boyang; XIA Yanfeng; FAN Diqing; FANG Yu (Jixie chuandong)
ObjectiveAiming at the work problem of installation quality acceptance of horizontal glass insulators in 500 kV transmission lines, a design scheme of a robot mechanism for insulator installation quality acceptance was proposed.MethodsFirstly, a three-dimensional model of the insulator acceptance robot was established based on the operating environment. The D-H parameter method was used to conduct forward kinematics analysis of the detection structure. Then, in order to solve the problem of the robot’s stable crawling on insulator strings with different tilt angles, the optimization of the robot’s driving structure was carried out, and kinematic simulations were carried out on insulator strings with three different tilt angles of 5°, 10° and 15°. Finally, the longitudinal and lateral stability of the optimized crawler robot were analyzed, and the force of the shock absorbing spring was simulated and analyzed.ResultsThe simulation results show that compared with the multi-wheeled drive structure, the stability of the robot’s center of mass in the crawler drive structure in the Z-axis speed is increased by 84.73％, 75.76％, and 73.70％ respectively; the stability of the X-axis offset distance is increased by 40.47％, 44.21％, and 74.14％ respectively, verifying that the optimized robot has better stability. The proposed scheme provides theoretical support for the overall design of the subsequent insulator robot.